Rare morbidity of permanent quadriplegia caused by neurenteric cyst of the cervical cord - Henry Tan Chor Lip; Tan Jih Huei; Ariz Chong Abdullah; Noor Azman Bin Rahman (Avicenna Journal of Medicine, 2019)
The incidence of neurenteric cyst (NC) is rare, accounting for 0.3%–1.3% of all spine tumors. The occurrence of quadriplegia caused by NC is even scarcer. Herein we report on a young girl with a rare NC over the C2-C5 spinal cord, which led to the morbidity of permanent quadriplegia despite early surgical intervention. This case highlights the rare morbidity of cervical cord NC presenting with permanent quadriplegia that failed to respond despite early surgical excision.